Ação da suplementação prévia de vitamina c e L-arginina em ratos Wistar submetidos ao quimioterápico 5-fluorouracil: aspectos moleculares e morfológicos nos testículos - Martins, Luiz Gustavo Peron (2023)
The cytotoxic chemotherapy drug 5-fluorouracil (5-FU) is commonly administered for the treatment of different types of neoplasms. One of the important limitations of using 5-FU is its toxicity to healthy proliferating cells, such as cells of the male reproductive system. Some supplements can be used to mitigate the toxic effects of 5-FU, such as L-arginine and vitamin C. This thesis was divided into two chapters. Chapter I is a literature review on the chemotherapy drug 5-FU and its toxicity to male reproductive organs, in addition the review presents Vitamin C and L-arginine as possible supplements prior to chemotherapy with the intention of reducing the deleterious effects of 5-FU to the reproductive organs. Chapter II is a scientific research that describes the experiment carried out with the application of 5-FU and supplementation of L-arginine and vitamin C in Wistar rats. The objective of Chapter I was to review the main toxic effects of 5-FU chemotherapy in non-cancer cells, with emphasis on reproductive organs, and also to present what is known about the antioxidant action of vitamin C and L-arginine, which justifies the study of these dietary supplements as alternatives to reduce 5-FU damage. The aim of Chapter II was to verify the effects of L-arginine and vitamin C supplementation, alone or in combination, on testicular and sperm morphology, on the gene expression of mediators related to oxidative stress and inflammation (Tnfα, Cat e Gss), on the expression of proteins linked to apoptosis (Caspase 3, BAX and BCL2) from testicular cells of rats submitted to 5-FU chemotherapy. The experiment in Chapter II was carried out using 40 Wistar rats that were divided into 5 groups with 8 animals each: Control group (Gc): rats received water and commercial feed ad libitum until the 7th day and application of saline solution on the 8th day of experiment; 5-FU Group (G5-FU): the rats received water and food ad libitum until the 7th day, on the 8th day of the experiment they received intraperitoneal application of a single dose of 5-FU (50 mg/Kg of body weight); 5-FU + L-arginine group (G5-FU+Arg): the rats received 213 mg of L-arginine/day added to filtered water ad libitum until the 7th day of the experiment, and on the 8th day of the experiment they received a single intraperitoneal application of 5-FU (50 mg/Kg of body weight); 5-FU + Vitamin C group (G5-FU+VitC): the rats received 5.71 mg of ascorbic acid/day added to filtered water ad libitum until the 7th day of the experiment, and on the 8th day of the experiment they received a single intraperitoneal application of 5-FU (50 mg/Kg of body weight); 5-FU + L-arginine + Vitamin C Group (G 5-FU+Arg+VitC): rats received 213 mg of L-arginine and 5.71 mg of ascorbic acid/day added to filtered water ad libitum until the 7th day and they received intraperitoneal application of a single dose of 5-FU (50 mg/Kg of body weight) on the 8th day of the experiment. Euthanasia was performed 72 hours after 5-FU application. After the euthanasia of the animals, the spermatozoa were used for sperm morphology and the testes were used for testicular morphology and morphometry, gene expression of mediators related to oxidative stress, expression of proteins linked to cellular apoptosis. There was a reduction of seminiferous tubules without morphological alterations in the G5-FU and G5-FU+Arg+VitC groups, accompanied by an increase in vacuoles in the seminiferous tubules; the G-5FU+Arg and G5-FU+VitC groups did not differ from the Gc in these parameters (P<0.05). The G5-FU+Arg+VitC group showed greater testicular degeneration than the other groups (P<0.05). There was a significant reduction in the height of the seminiferous epithelium in the G-5FU+Arg and G5-FU+Arg+VitC groups. There was no significant difference in sperm morphology. G5-FU showed greater BAX expression in the testes of Wistar rats than Gc, and G5-FU+VitC did not differ from the control group (P<0.05). The application of a single dose of 5-FU leads to an increase in testicular pathologies and the preventive supplementation of vitamin C, without the association of L-arginine, reduces the deleterious effects of 5-FU on the testicles of Wistar rats.